Dynamic structural impacts of oil shocks on exchange rates: Lessons to learn - Qiang Ji; Syed Jawad Hussain Shahzad; Elie Bouri; Muhammad Tahir Suleman (Journal of Economic Structures, 2020)
This study explores the dynamic effects of different oil shocks on real exchange rates in net oil importers and exporters. Specifically, the connectedness measures are combined with the structural vector autoregressive model. The findings show that oil supply shocks have a larger depreciating influence on exchange rates in oil exporters than in importers. All countries are generally more sensitive to oil-specific demand shocks, and this sensitivity can lead to a significant appreciation in real exchange rates, except in Japan and the United Kingdom. Further, the spillover effect between oil shocks and exchange rates has strengthened after the global financial crisis of 2007-08. Our findings provide useful implications for the policy-makers and market risk managers to effectively avoid exchange rate risk induced by oil shocks.
Keywords: 330; Oil shocks; Exchange rate; Connectedness; Spillover effect